Faces of Palestine Issue: Religious Nationalism, Delegitimizing Citizenship, and Islam phobia - Dr. Muhammad Umar Riaz Abbasi; Dr. Samar Majid; Maryam Jamil; Dr. Shamaila Athar; Dr. Naseem Mahmood; Dr. Talib Ali Awan (Al-Qanṭara, 2023)
Whatever government administers historic Palestine must have legal citizens to be democratically legitimate. All people considerably, seriously, or existentially affected by the state's norms regulating the area must be considered legal citizens. The geographic territory between the Eastern Mediterranean & the Jordan River had been known as Palestine from the collapse of the Roman Empire in World War I until 1918. Since the start of the 20th century, the Arabs who dwell in this region have been referred to as Palestinians. According to the document, around half of Palestinians living outside the historic Palestinian borders are also adversely harmed, which is enough to justify claiming citizenship in any state that governs the territory, which can be referred to as their homeland. After many people have exercised their right to return, and all other people who reside in historic Palestine now have the democratic legitimacy to be termed a state, it will be a state of all Palestinians. So, this study was conducted to address the Palestinian people's issues.